Red-necked avocets disperse at continental scales and breed following high rainfall in distant locations - Rowan Mott; Thomas A. A. Prowse; Micha V. Jackson; Sonia Sanchez-Gomez; Andrew T. D. Bennett; Jody O’Connor; Daniel J. Rogers; Justin D. Brookes; Phillip Cassey (Scientific Reports)
Abstract Nomadic species present conservation challenges due to their dynamic use of habitats at broad spatial scales. We carried out the first tracking of Red-necked Avocets (Recurvirostra novaehollandiae), a nomadic waterbird, to document their movements as they dispersed from the Coorong (a coastal refuge that regularly supports > 5% of the global population) to core breeding areas in central Australia. Dispersal from the Coorong to wetlands in the Lake Eyre Basin was most likely soon after high seven-day rainfall in that basin (departure odds diminished 5.24% per additional day post-rainfall event), whereas dispersal to wetlands in the Murray-Darling Basin was not significantly associated with any local or distant rainfall patterns. Tracking revealed ten nesting attempts (from six individuals) spread across three Australian states. Only four attempts showed evidence of hatching. The three individuals tracked for > 1 year all returned to the Coorong, suggesting high site fidelity to this wetland. Consequently, long-term Coorong census data is likely to be a genuine index of Red-necked Avocet population abundance rather than reflecting flux of birds visiting only once. This work supports the conservation of a connected habitat network for this nomadic species, as site-based conservation measures are less effective if broader landscape context is ignored.